Clinical Profile and Outcome of Patients with Atrioventricular Block Admitted in a Tertiary Cardiac Care Centre in Nepal (Journal of Invasive and Clinical Cardiology, 2025)
Background: Atrioventricular block is generally caused by congenital and acquired causes; acquired causes are further divided into ischemic and non-ischemic etiologies. Majority of patients will get permanent pacemaker however few cases with reversible causes have good recovery of sinus rhythm. The main aim of this study is to determine the clinical profile and outcome of patients with atrioventricular block admitted in a tertiary cardiac care centre.Methods: This is prospective, observational study conducted at Shahid Gangalal National Heart Centre, Kathmandu, Nepal. Our study included 126 patients with atrioventricular block fulfilling inclusion criteria from June 1, 2023 to January 31, 2024.Results: 126 patients were enrolled for the study. Out of which 72 (57.1%) were males and 54 (42.9%) were females. Mean age of patient was 68.4±13.3 years. Most common presenting symptom was dizziness 81 (64.3%). Hypertension was the most common comorbid condition present in 73 (57.9%) of patients while 45 (35.7%) did not have any associated conditions. Complete heart block was the most common AV block documented, accounting for 108 (85.8%) of cases. Non ischemic etiology was found in 99 (78.6%) and ischemic etiology were found in 27 (21.4%) patients. Majority of patients 102 (81%) had undergone permanent pacemaker insertion, while only 3 (2.4%) death occurred during hospitalization. 21 (16.7%) patients recovered to sinus rhythm, majority (95.2%) belong to ischemic sub group.Conclusion: Non-ischemic causes of Atrioventricular block is common in clinical practice however, majority of patients with ischemic cause recovered to sinus rhythm.J Inv Clin Cardiol 2024; 6(1): 7-12